Understanding receptivity to informal supportive cancer care in regional and rural Australia: a Heideggerian analysis. (5th June 2015) - Pascal, J.; Johnson, N.; Dickson‐Swift, V.; McGrath, P.; Dangerfield, F.
Abstract : The concept of receptivity is a new way of understanding the personal and social factors that affect a person living with and beyond cancer, and how these factors influence access to formal supportive care service provision and planning. This article contributes to new knowledge through applying the concept of receptivity to informal supportive cancer care in regional Australia. Literature indicates that a cancer diagnosis is a life‐changing experience, particularly in regional communities, where survival rates are lower and there are significant barriers to accessing services. Heideggerian phenomenology informed the design of the study and allowed for a rich and nuanced understanding of participants lived experiences of informal supportive cancer care. These experiences were captured using in‐depth interviews, which were subsequently thematically analysed. Nineteen participants were recruited from across regional Victoria, Australia. Participants self‐reported a range of stages and types of cancer. Significantly, findings revealed that most participants were not referred to, and did not seek, formal supportive care. Instead, they were receptive to informal supportive care. Understanding receptivity and the role of anxiety and fear of death has implications for partners, family, community members, as well as professionals working with people with living with and beyond cancer.